Exercise-induced fatigue impairs change of direction performance and serve precision among young male tennis players - Bilic, Z.; Sinkovic, F.; Barbaros, P.; Novak, D.; Zemkova, E. (Sports, 2023)
This study investigates the effect of exercise-induced fatigue on change of direction performance and serve precision among young tennis players. A group of 21 players (age 12.90 ± 0.76 years), ranked among the top 50 players on the national tennis federation scale and the top 300 on the "Tennis Europe" scale, participated in the study. They underwent a standardized physiological load protocol using the "300-m running test" which consists of consecutive runs for 15 shares of 20 m (15 × 20). Its intensity was determined using the Borg Rating of Perceived Exertion (RPE) scale where subjects evaluated their level of experienced load on a scale from 0 to 10. Prior to and after the protocol, they performed a pre-planned change of direction T-test and serve precision test. Results showed significant increase of time in the T-test (from 11.75 ± 0.45 s to 12.99 ± 0.4 s, p = 0.00) and decrease in serve precision parameter from (6.00 ± 1.04 to 4.00 ± 1.26, p = 0.00) after the fatigue test protocol. The RPE increased from 5 to 9, after the fatigue protocol, indicating the desired fatigue effect. These findings indicate that exercise-induced fatigue impairs change of direction performance and serve precision among young tennis players.